2018
DOI: 10.1016/j.jconrel.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Injectable and protease-degradable hydrogel for siRNA sequestration and triggered delivery to the heart

Abstract: Injectable hydrogels have significant therapeutic potential for treatment of myocardial infarction (MI) through tissue bulking and local drug delivery, including the delivery of small interfering RNAs (siRNAs). As siRNA targets are identified as potential treatments for MI, hydrogels may bolster efficacy through local and sustained release. Here, we designed an injectable hydrogel to respond to local upregulation in proteolytic activity after MI to erode and release siRNA against MMP2 (siMMP2), a target implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 58 publications
1
84
0
Order By: Relevance
“…The controlled release of small molecules, proteins, and growth factors from CD‐based hydrogels has been widely investigated, whereas release kinetics can be tuned through porosity, mesh size, and degradation . More recently, CD‐based hydrogels were developed as gene carriers, including with β‐cyclodextrin‐modified polyethylenimine (PEI) and adamantane‐modified PEG for local siRNA release to the infarcted myocardium . The modified polymers assembled with siRNA to form hydrogels that released polyplexes for transfection.…”
Section: Physical Associations To Assemble Hydrogelsmentioning
confidence: 99%
“…The controlled release of small molecules, proteins, and growth factors from CD‐based hydrogels has been widely investigated, whereas release kinetics can be tuned through porosity, mesh size, and degradation . More recently, CD‐based hydrogels were developed as gene carriers, including with β‐cyclodextrin‐modified polyethylenimine (PEI) and adamantane‐modified PEG for local siRNA release to the infarcted myocardium . The modified polymers assembled with siRNA to form hydrogels that released polyplexes for transfection.…”
Section: Physical Associations To Assemble Hydrogelsmentioning
confidence: 99%
“…In recent years, injectable hydrogels, a kind of promising synthetic biomaterials with advantages of mild gelation and cardiac-compatible properties [34,35], have been proved to improve cardiac function after local myocardial injection alone [36]. In addition, hydrogels can also encapsulate therapeutic drugs, deliver them to target areas, and subsequently achieve continuous therapeutic effects [37]. Therefore, hydrogels may become a kind of more attractive method of exogenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the injection of hydrogel in ischaemic areas after MI could promote cardiac repair and improve cardiac function [42]. Hydrogels can also encapsulate therapeutic drugs and deliver them to target areas to achieve sustained therapeutic effects [43]. Steele et al [44] encapsulated two cytokines, dimeric fragment of HGF and engineered stromal cell-derived factor 1α, in hydrogels and delivered them to the peri-infarct regions, and found that the release time of the cytokines was signi cantly prolonged and the therapeutic effects were enhanced when the cytokines were encapsulated in hydrogels.…”
Section: Discussionmentioning
confidence: 99%